IMPAIRED RENAL FUNCTION IN COVID-19 INFECTION - Dilrukh Kh. Madazimova; Ozimbay O. Jabbarov; Laylo D. Tursunova (Central Asian Journal of Medicine, 2024)
The SARS-CoV-2 virus (COVID-19) is highly contagious, virulent and shows tropism to many cells of human organs. To enter the cell, the SARS-CoV-2 virus uses the angiotensin converting enzyme type 2 (APV2) receptor, which is highly expressed in the kidneys. Through the APF2-dependent signaling pathway, SARS-CoV-2 can directly infect the epithelium of the renal tubules and podocytes.